PLOJDY ANALYSIS AND DNA CONTENT OF MUTANT BANAN "PISANG BERANGAN" USING FLOW CYTOMETRY - ROFINA YASMIN OTHMAN; ABDELGADIR RAYIS SHADIA; MAK CHAI (BIOTROPIA, 2002)
Mutagens cause random changes in the nuclear DNA or cytoplasmic organelles, resulting in gene, chromosomal or genomic mutations and hence, create variability. In this study, flow cytometry (FCM) was used to determine ploidy levels and DNA content in gamma-irradiated variants of mutated Pisang Berangan (cv. Intan, AAA) - a local banana genotype. Induced variants such as short plant stature (stunted growth), late flowering plants (late maturity) and abnormalities in bunch characters were selected to study possible changes at the DNA level. The study showed that DNA content of mutated plants differed from non-irradiated control and that irradiation had the most effect at high doses (40 and 60 Gy). The increase of DNA content in 20 Gy and 30 Gy treated plants was not more than that of the control plants. The values of genomic DNA content of gamma-irradiation variants decreased as the dose of irradiation increased from 20 to 60 Gy, indicating that the high dose of gamma-irradiation had a significant effect on the genome of the plants. The analysis further showed that phenotypic variation due to mutagenesis was reflected in the DNA content of the plants. The results also showed that ploidy levels were not affected by gamma-irradiation even at high doses. Keywords: Musa spp./mutation breeding/ flow cytometry/Â  ploidy level/ DNA content